Gender Differentials in Labor Market Outcomes: Exploring the Impact of Gender Differences on Labor Market Outcomes (Journal of Advances and Scholarly Researches in Allied Education, 2012)
We discuss the experimental literature to the understanding of both traditional and before uncultivated proportions of gender differences and talk about their bearings on labor market outcomes. Experiments have offered new findings on gender discrimination, and while they have recognized a bias alongside hiring women in some labor market segments, the discrimination detected in field experiments is less pervasive than that indirect by the regression approach. Experiments have also offered new insights into gender dissimilarity in preferences: women appear to increase less from negotiation, have lower preferences than men for risk and competition, and may be more sensitive to social cues. These gender differences in preferences also have implications in group settings, whereby the gender composition of a grouping affects team decisions and performance. Most of the evidence on femininity traits comes from the lab, and key open query remain as to the source of gender preferences—nature versus nurture, or their interaction—and their role, if any, in the workplace.